International Electron Devices Meeting 1998. Technical Digest (Cat. No.98CH36217)
DOI: 10.1109/iedm.1998.746443
|View full text |Cite
|
Sign up to set email alerts
|

High-gain GaInP/GaAs HBT monolithic transimpedance amplifier for high-speed optoelectronic receivers

Abstract: A self-aligned GaInF'/GaAs HBT technology was used to develop a monolithic high-gain transimpedance amplifier suitable for optical communication receivers. On-wafer probe measurements revealed a gain (SZJ of 18.8 dB with a bandwidth of 13.5 GHz and input, output matching better than -8 dB. The am lifier showed a sensitivity of -15 dBm for 10 Gb/s NRZ 2 -1 pseudo-random bit sequence with a BER ofThe noise figure of the amplifier was better than 7.5 dB over the bandwidth of operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Transimpedance gain of optical receivers expressed in dBΩ can be found from the S-parameters of the amplifier based on the following equation [4]. Note that the gain of a perfect through line (S 21 =1) matched at both ends is about 34dBΩ.…”
Section: Design Of the Transimpedance Amplifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Transimpedance gain of optical receivers expressed in dBΩ can be found from the S-parameters of the amplifier based on the following equation [4]. Note that the gain of a perfect through line (S 21 =1) matched at both ends is about 34dBΩ.…”
Section: Design Of the Transimpedance Amplifiermentioning
confidence: 99%
“…The advantages of using integrated optical receivers are their smaller size, and higher data rate for a given optical power sensitivity, when compared with their hybrid counterparts. The drawbacks of using integrated optical receivers are the high cost associated with integrating photodiode and transistor technology and tradeoffs between the speed of the transistor and the sensitivity of the photodiode when utilizing a common heterostructure approach [1]- [4]. Integrated Photo-detectors based on Silicon CMOS technology have been recently reported in the literature for visible spectrum [5][6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…GaInP/GaAs heterojunction bipolar transistors (HBTs) grown by MOCVD have been first demonstrated by the authors [3], and this technology is currently accepted as a superb alternative to AlGaAs/GaAs HBTs due to the absence of Al, the excellent etching selectivity, and better reliability characteristics [4], [5]. Monolithic broadband GaInP/GaAs HBT transimpedance amplifiers having a bandwidth (BW) of 19 GHz have been demonstrated by the authors and their large signal, as well as, a high gain performance have been reported [6], [7]. Excellent microwave performance of 140~GHz and GHz has been achieved using GaInP/GaAs HBTs [8], and chemical beam epitaxy (CBE) using TBA/TBP precursors has been reported for growth of GaInP/GaAs devices [9].…”
Section: Introductionmentioning
confidence: 99%